The Impact of Active Listening on Student Engagement and Learning Outcomes in Educational Settings - Paramole, Oyeronke Christiana; Adeoye, Moses Adeleke; Arowosaye, Saheed Abiodun; Ibikunle, Yejide Adepeju (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Active listening is a crucial skill in education, fostering meaningful communication between educators and students. This paper explores the theoretical foundations of active listening, including historical developments and key models such as those proposed by Carl Rogers and Stephen Covey. Empathy, a core component of active listening, is examined for its role in enhancing student engagement and creating a supportive learning environment. The paper also discusses the implications of active listening within various learning theories, including constructivism, social learning, and transformative learning. In expanding the theoretical framework, relevant philosophical perspectives are integrated. Phenomenology emphasizes understanding individual experiences, which can strengthen teacher-student relationships. Pragmatism positions active listening as a tool for practical problem-solving, enhancing real-world learning applications. Existentialism highlights the importance of authenticity and self-expression in communication, promoting personal growth among students. Lastly, critical pedagogy underscores the significance of dialogue in education, advocating for active listening as a means to empower students. Through this comprehensive exploration, the paper illustrates how active listening not only improves classroom dynamics but also equips students with essential communication skills. By recognizing and addressing barriers to effective listening, educators can create an inclusive environment that values every student’s voice. In conclusion, active listening emerges as a transformative practice that supports both academic success and personal development in the educational landscape.